Recovery of a Surf Clam Donax deltoides Population in Southern Australia: Successful Outcomes of Fishery‐Independent Surveys. (30th November 2015) - Ferguson, Greg J.; Ward, Tim M.; Gorman, Daniel
Abstract: Estimates of biomass or relative biomass are required for monitoring the recovery of depleted bivalve resources and for the management of newly exploited resources. Uncertainty around fishery catch per unit effort (CPUE) as a proxy for biomass highlights the need for fishery‐independent assessments. Following a prolonged period of decline in Australia's largest fishery for surf clam Donax deltoides, robust estimates of biomass were required to monitor recovery and to set appropriate total allowable commercial catches. Estimates of relative biomass were derived from fishery‐independent surveys (FIS) conducted cooperatively by researchers and fishers. The FIS assessed both the spatial (m to km) and temporal (months to years) dynamics of the fishery and enabled comparisons with CPUE. Concurrent size‐frequency distributions provided information on the mechanisms underlying variability in resource status across the fishery. Increasing relative biomass and complexity of size structures indicated recovery of the resource from 2009, although spatial contraction of the resource also occurred. Relative biomass from FIS provides a robust fishery performance indicator that is appropriate to the scale of the fishery and has advantages over fishery‐dependent CPUE of finer temporal and spatial resolution and consistent sampling efficiency. Performance indicators based on FIS provide improved understanding of the changes in resource status. Active engagement of fishers contributes to enhanced economic and environmental outcomes. Received December 9, 2014; accepted September 3, 2015